Estimation of direct and maternal (co)variance components for lactation traits in Jersey crossbred cattle at an organized farm - RATWAN, POONAM; KUMAR, MANOJ; CHAKRAVARTY, A K; MANDAL, AJOY (The Indian Journal of Animal Sciences, 2019)
Genetic parameters and (co)variance components were estimated for 305 days milk yield (305DMY), total milk yield (TMY), lactation length (LL) and peak yield (PY) in an organized herd of Jersey crossbred cattle. Restricted maximum likelihood (REML) fitting an animal model and ignoring or including maternal genetic or permanent environmental effects was used for carrying out analyses. Six different animal models were fitted for all traits. The best model was chosen after testing the improvement of log-likelihood values. Direct heritability estimates were 0.55, 0.50, 0.25 and 0.41 for 305DMY, TMY, LL and PY, respectively. Maternal genetic effects contributed 9 and 17% of the total variance for 305DMY and PY, respectively. Results suggest that maternal additive effect was important for 305 days milk yield and peak yield whereas permanent environmental maternal effects did not contribute to the total phenotypic variance of the considered traits in our study. Moderate to high direct heritability estimates varying from 0.25 to 0.55 for all considered lactation traits in this study suggests that there is adequate scope of improvement for these traits through selection under the prevailing management conditions. Further, for 305 days milk yield and peak yield maternal heritability was found to be imperative indicating that for improving these traits through selection both direct additive as well as maternal genetic effect must be taken into consideration.